PENGGUNAAN MULTIMEDIA BERBASIS VISUAL DALAM UPAYA MENINGKATKAN MINAT BELAJAR PENDIDIKAN PANCASILA SISWA KELAS XI-6 SMA NEGERI 1 GOWA - Nur Rahmat; Rismawati; Sri Murwanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
This research aims to explore efforts to enhance students' interest in learning Pancasila Education through the use of visual-based multimedia. The method applied in this study is collaborative action research, which requires cooperation with other parties such as superiors, peers, or colleagues. Data analysis results indicate that the use of visual-based multimedia in Classroom Action Research can specifically increase students' interest in learning. Interest in learning plays a crucial role in the educational process and affects the achievement of learning goals. Therefore, interest in learning is a key factor for students' academic success. The research results, after going through the first and second cycles, show that the interest in learning among students in class XI-6 at SMAN 1 Gowa has started to show positive results. Students have begun to show interest in learning Pancasila Education, and the grades obtained also reflect an improvement, indicating the students' seriousness in learning. The increase in students' interest in learning has occurred gradually, as seen in the first and second cycles, demonstrating significant progress due to the various efforts that have been made.